8.8 Neonatal Encephalopathy in the Cooling Therapy era – Preliminary Cerebral Magnetic Resonance results from the Marble Consortium. (9th June 2014) - Pauliah, SS; Lally, PJ; Bainbridge, A; Price, DL; Addison, S; Cowan, FM; Satodia, P; Wayte, SC; Soe, A; Pattnayak, S; Harigopal, S; Abernethy, LJ; et al.
Abstract : Background: Although cerebral metabolic changes during neonatal encephalopathy (NE) have been well characterised using magnetic resonance spectroscopy (MRS) in single-centre studies, the widespread effect of therapeutic hypothermia is less clear. Objective: To describe patterns of brain injury in a prospective multi-centre cohort of infants with NE who had rescue hypothermic neuroprotection. Design: After MRS harmonisation on 3T MR scanners (Phillips, GE, Siemens), at six participating sites we performed magnetic resonance imaging (MRI) and MRS (single-voxel PRESS, 15 x 15 × x 15 mm 3 thalamic voxel, TR = 2s/TE = 288 ms) on infants <2 wks who had whole-body cooling for NE at any of the MARBLE centres. We used jMRUI to process MRS data and calculate metabolite peak-area ratios. Results: Forty-three infants were recruited; 11(26%) had mild, 26(60%) moderate and 6(14%) had severe NE (<6h Sarnat staging). Moderate/severe basal ganglia and cortex were detected by MRI in 4(9%) and 1(2%) cases respectively, and 15(34%) had moderate/severe white matter injury. Thirteen (30%) had normal MRI. Elevations in lactate (Lac)/N-acetylaspartate (NAA) were noted in 6(13%) cases, Lac/choline (Cho) in 5(11%) and Lac/ creatine (Cr) in 8(18%). MRS was normal in 28(65%) infants. Conclusions: In this predominantly moderate NE cohort, white matter injury was most common, and the majority had normal MRS metabolite ratios. Ongoing work seeks to establish whether these brain injury patterns are characteristic in the cooling therapy era.